Numerical study of sediment suspension affected by rigid cylinders under unidirectional and combined wave–current flows - Lou, Sha; Chen, Xiaolan; Zhou, Shengyu; Ma, Gangfeng; Liu, Shuguang; Radnaeva, Larisa Dorzhievna; Nikitina, Elena; Fedorova, Irina Viktorovna (Frontiers in Marine Science, 2023)
Sediment transport modeling for flows with cylinders is very challenging owing to the complicated flow–cylinder–sediment interactions, especially under the combined wave-current flows. In this paper, an improved formulation for incipient sediment suspension considering the effect of cylinder density (i.e., solid volume fraction) is employed to simulate the bottom sediment flux in the flow with cylinders. The proposed model is calibrated and validated using laboratory measurements under unidirectional and combined wave-current flows in previous studies. It is proved that the effects of cylinders on sediment suspension can be accounted for through a modified critical Shields number, and the proposed model is capable of simulating sediment suspension under both unidirectional and combined wave–current flows reasonably well with the average the coefficients of determination and model skills greater than 0.8 and 0.64.